First and second order analysis of functionally graded composite material. (2022) - Sharma, Rajesh; Jadon, Vijay Kumar; Singh, Balkar; Kumar, Rajneesh; Kumar, Sanjeev
Abstract: This paper deals with the analysis of metal-ceramic (FGM) rectangular composite plate under transient loading conditions. Fully-Coupled Thermal-stress Transient analysis has been carried out and convergence study for peak stress and central deflection for various mesh size has been carried out and compared for both first and second order quad elements. Abaqus subroutine USDFLD has been used for spatially varying material properties of the FGM material. Volume fraction of the two constituents of the FGM is varied smoothly based on the power law for various values of porosity coefficient. Exponentially time varying temperature loading on the top and bottom surface of the FGM plate is considered with simply supported boundary conditions.